2012
DOI: 10.1080/09540121.2011.648603
|View full text |Cite
|
Sign up to set email alerts
|

Risks worth taking: Safety agreements among discordant gay couples

Abstract: As HIV research and prevention efforts increasingly target gay men in relationships, situational factors such as couple serostatus and agreements about sex become central to examinations of risk. Discordant gay couples are of particular interest because the risk of HIV infection is seemingly near-at-hand. Yet little is known about their sexual behaviors, agreements about sex, and safer sex efforts. The present study utilized longitudinal semi-structured, qualitative interviews to explore these issues among 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 42 publications
0
32
1
Order By: Relevance
“…However, some YMSM were found to report low condom use with both their main regular and casual partners. This contradicts previous research and troubles presumptions about strategically-deployed condom use (Beougher et al, 2012); it also supports recent findings that highlight the challenge in negotiating sexual experiences and maintaining sexual agreements between partners (Adam, 2006).…”
Section: Implications and Future Researchcontrasting
confidence: 46%
See 1 more Smart Citation
“…However, some YMSM were found to report low condom use with both their main regular and casual partners. This contradicts previous research and troubles presumptions about strategically-deployed condom use (Beougher et al, 2012); it also supports recent findings that highlight the challenge in negotiating sexual experiences and maintaining sexual agreements between partners (Adam, 2006).…”
Section: Implications and Future Researchcontrasting
confidence: 46%
“…Young men who indicated they had sex with at least four additional regular partners in the past six months were significantly less likely to report high condom use with their boyfriend with whom they had the most sex compared with participants who reported a single boyfriend. Despite low condom use with their primary boyfriend, if these participants were consistently using condoms with their other regular partners, this may represent negotiated safety (Beougher et al, 2012). However, given the previous discussion of habitual nonuse of condoms across main regular and casual partners by some YMSM, this could also represent a potential behavioral nexus of high risk for HIV acquisition and forward transmission (frequent sex, multiple partners, and low condom use) between regular sex partners.…”
Section: Discussionmentioning
confidence: 70%
“…Yet few models exist that MSM couples may use to navigate the disclosure of breaks when they happen. 13,21,[30][31][32][33] In addition, Interdependence Theory posits that men prioritize the needs of their relationship over their personal health when making decisions-which could make negotiation and/or disclosure of broken agreements even more difficult. 34,35 These complexities between individual and partner-level priorities highlight the need to examine the influence of relationship dynamics on sexual risk behavior in MSM couples.…”
Section: Introductionmentioning
confidence: 99%
“…20 Finally, MSM in relationships may experience condom fatigue or mistakenly perceive themselves to be low risk due to their relationship status or access to new biomedical interventions. 1,11,[21][22][23][24][25] While the literature lays the foundation for understanding HIV risk for MSM couples, much of it fails to include both partners and few studies attempt to account for the relationship dynamics above.…”
Section: Introductionmentioning
confidence: 99%
“…In concert with a move to no longer use condoms, the heightened level of trust signified by monogamy consolidated the intimacy and significance of a couple's love. Previous research has indicated that men in relationships are motivated to give up using condoms due to such feelings as increased intimacy, trust, love, and sexual pleasure, and that familiarity with a partner, assumed knowledge of serostatus and use of alternative risk-reduction strategies mediate their calculations of risk (Beougher et al, 2012;Mitchell et al, 2012;Prestage et al, 2006). Among these men, the risks of HIV implicitly raised the stakes of their relationships, while creating a space in which they could share their "true" self.…”
Section: Discussionmentioning
confidence: 95%